Martín de Porres : the rose in the desert - Schmidt, Gary D. (Clarion Books/Houghton Mifflin Harcourt, 2012)
The story of Saint Martin de Porres--an endearing tale of perseverance, faith, and triumph over racial and economic prejudice.